2021
DOI: 10.3390/agronomy11020349
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Comparisons of Heirloom and Modern Processing Tomato Genotypes Cultivated in Organic and Conventional Farming Systems

Abstract: The yield and fruit quality of processing tomatoes (Solanum lycopersicum L.) have increased markedly over the past decades. The aim of this work was to assess the effects of the organic (OFS) and conventional farming systems (CFS) on the main agronomic parameters involved in processing tomato yield components and fruit quality traits of heirloom and modern genotypes. Marketable yield increased from heirloom to modern genotypes, both in OFS and in CFS, showing a difference of ≈20 t per hectare in favor of CFS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
3
Order By: Relevance
“…When comparing the productive yield of fertilization (organic × mineral fertilizer), there is generally a notable superiority for chemical fertilization 38 , but on the other hand, the organic fertilizer has shown a higher LAI when compared to other polymers used in the market 39 . Experiments carried out with cultivars showed a higher LAI under mineral fertilizer, but some cultivars showed a higher index within the organic fertilizer, thus demonstrating the existence of cultivars better adapted to the organic material as fertilizer 40 . However, the different types of organic fertilization tested in the experiment tended to show a higher leaf area index compared to the mineral fertilization 41 .…”
Section: Discussionmentioning
confidence: 92%
“…When comparing the productive yield of fertilization (organic × mineral fertilizer), there is generally a notable superiority for chemical fertilization 38 , but on the other hand, the organic fertilizer has shown a higher LAI when compared to other polymers used in the market 39 . Experiments carried out with cultivars showed a higher LAI under mineral fertilizer, but some cultivars showed a higher index within the organic fertilizer, thus demonstrating the existence of cultivars better adapted to the organic material as fertilizer 40 . However, the different types of organic fertilization tested in the experiment tended to show a higher leaf area index compared to the mineral fertilization 41 .…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, it has been documented that tomato plants under organic farming undergo moderate environmental stress [ 11 ], causing lower fruit yields [ 12 , 13 , 14 , 15 , 16 ], a reduction in fruit weight and firmness [ 14 , 16 ], and an increase in phytopathogen infections [ 9 , 17 ], compared to conventional production systems. Interestingly, it has been suggested that a potential cause of the agricultural problems observed in organic production could be associated with alterations of the tomato plant microbiota [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…El jitomate (Solanum lycopersicum L.) es una de las hortalizas de mayor importancia económica en el mundo, presenta una tasa de incremento anual en el rendimiento de fruto de 2.4% (Ronga et al, 2021). Es el segundo vegetal más cultivado por la humanidad debido a su contenido de compuestos funcionales, sabor, aroma y color de la pulpa del fruto (Casals et al, 2021).…”
Section: Introductionunclassified
“…En la actualidad el humano está cambiando sus hábitos alimenticios y tiene preferencia por alimentos orgánicos, nutraceúticos, de mayor calidad y libres de residuos químicos (Melotto et al, 2020). Estas exigencias deberían incorporarse en los nuevos objetivos de la mejora genética del jitomate (Ronga et al, 2021).…”
Section: Introductionunclassified